Comparative evaluation of intraligamentary injection and traditional inferior alveolar nerve block in endodontic management of mandibular molar with symptomatic irreversible pulpitis: A randomized double-blinded clinical trial - Deepashri Tekam; Chetana S Makade; Pratima R Shenoi; Mohit K Gunwal (Asian Journal of Medical Sciences, 2024)
Background: Intraligamentary anesthesia (ILA) injection using a single-tooth anesthesia (STA) system has been used as a supplementary technique for pulpal anesthesia in cases of irreversible pulpitis.